2013
DOI: 10.1016/j.ijom.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Do erupted third molars weaken the mandibular angle after trauma to the chin region? A 3D finite element study

Abstract: It has been suggested that third molars increase mandibular fragility because they do not contribute to its strength. For ethical reasons, a human study design that would permit the elucidation of this interference is not possible. This study evaluated the impact of the presence of erupted third molars on the mandibular angle of resistance when submitted to trauma. A three-dimensional (3D) mandibular model was obtained through finite element methodology using computed tomography (CT) with the geometry and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 20 publications
3
60
0
8
Order By: Relevance
“…As punches often hit the mandible, this may well be the reason for the high number of wisdom teeth involved; wisdom teeth play an important role as a weak point in the mandible, making it prone for fractures of the mandibular angle (26)(27)(28).Motor vehicle accidents in our study totaled only 13%. Given that this group plays the main role for dental or maxillofacial traumatization in studies (15,18,29) from other countries, this number might be an argument for the high security standard, including the obligation to buckle up or wear protective headgear as a motorcyclist.…”
Section: Discussionmentioning
confidence: 70%
“…As punches often hit the mandible, this may well be the reason for the high number of wisdom teeth involved; wisdom teeth play an important role as a weak point in the mandible, making it prone for fractures of the mandibular angle (26)(27)(28).Motor vehicle accidents in our study totaled only 13%. Given that this group plays the main role for dental or maxillofacial traumatization in studies (15,18,29) from other countries, this number might be an argument for the high security standard, including the obligation to buckle up or wear protective headgear as a motorcyclist.…”
Section: Discussionmentioning
confidence: 70%
“…The young modulus can be calculated using different equation. In the literature, the young modulus of cortical bone ranges between 13-39 GPa [5,11,12], and the young modulus of cancellous bone ranges between 500 and 1500 MPa [12]. The situation shows that the obtained values of young modulus for cortical and cancellous bone are available value and can be used as mechanical properties for FEA simulation.…”
Section: Fig 13 Young Modulus Of Cortical and Cancellous Regionsmentioning
confidence: 99%
“…The mandible is one of the bones most susceptible to trauma in the facial region due to its more projected position in the facial skeleton [5]. The biomechanical behavior of the mandible is very important in various clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…FEA is a numerical approach that addresses the complexity of the modeling by deriving an approximation to the solution. FEA has been used previously to evaluate the treatment of facial fractures [1][2][3][4][5]. Especially, O. Atali et al reported strong correlation between FEA and experiments [2].…”
Section: Introductionmentioning
confidence: 99%